A Combinatorial Optimisation of Rater Allocation (Cora): A Discrete Algebraic Formalism for Round-Robin Scheduling In High-Stakes Speaking Assessment - Norazha Paiman; Wan Nur ‘Ashiqin Wan Mohamad (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia